Civil engineering materials - Sivakugan, N.; Gnanendran, Carthigesu T.; Tuladhar, Rabin; Kannan, M. Bobby (Cengage Learning, 2018)
Civil engineering materials explains why construction materials behave the way they do. The book concentrates on demonstrating methods to obtain, analyse and use information rather than focusing on presenting large amounts of data. Beginning with basic properties of materials, it moves on to more complex areas such as the theory of concrete durability and corrosion of steel.